2020
DOI: 10.1111/1462-2920.15136
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatase‐associated protein MoTip41 interacts with the phosphatase MoPpe1 to mediate crosstalk between TOR and cell wall integrity signalling during infection by the rice blast fungus Magnaporthe oryzae

Abstract: Summary The type 2A (PP2A) and type 2A‐like (PP4 and PP6) serine/threonine phosphatases participate in a variety of cellular processes, such as cell cycle progression, signal transduction and apoptosis. Previously, we reported that the PP6 catalytic subunit MoPpe1, which interacts with and is suppressed by type 2A associated protein of 42 kDa (MoTap42), an essential protein involved in the target of rapamycin (TOR) signalling pathway, has important roles in development, virulence and activation of the cell wal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 49 publications
0
22
0
Order By: Relevance
“…The previous studies reported that the SNF1, cAMP-PKA and TOR signaling pathways regulate sporulation in numerous species of filamentous fungi, at the cellular and molecular levels [ 30 , 185 , 200 , 237 , 238 ]. Rapamycin treatment and inactivation TOR can induce the biogenesis of lipid droplet required for triacylglycerol accumulation, whereas PKA regulates the degradation of triacylglycerol and SNF1 regulates the lipid mobilization required for fungal development and sporulation [ 29 , 92 , 112 , 185 , 187 , 200 ].…”
Section: Resultsmentioning
confidence: 99%
“…The previous studies reported that the SNF1, cAMP-PKA and TOR signaling pathways regulate sporulation in numerous species of filamentous fungi, at the cellular and molecular levels [ 30 , 185 , 200 , 237 , 238 ]. Rapamycin treatment and inactivation TOR can induce the biogenesis of lipid droplet required for triacylglycerol accumulation, whereas PKA regulates the degradation of triacylglycerol and SNF1 regulates the lipid mobilization required for fungal development and sporulation [ 29 , 92 , 112 , 185 , 187 , 200 ].…”
Section: Resultsmentioning
confidence: 99%
“…MoRS3 , which encodes a ribosomal subunit, is transcriptionally regulated based on MoTor activity. Furthermore, the gene expression levels of MoTOR and the MoTOR ‐regulating gene MoRS3 were examined by quantitative reverse transcription PCR (RT‐qPCR) (Qian et al, 2020 ). The results showed that both MoTOR and MoRS3 were up‐regulated in the Δ Mowhi2 and Δ Mopsr1 strains compared with those in the WT strain (Figure 8c,d ), suggesting that the transcriptional level and enzyme activity were up‐regulated after knockout of MoWHI2 and MoPSR1 .…”
Section: Resultsmentioning
confidence: 99%
“…The TOR kinase complex is an evolutionarily conserved protein kinase, coordinating nutrients and energy to regulate cell proliferation, the cell cycle, cell wall integrity, and cell metabolic activities by interacting with different subunits (Gonzalez & Hall, 2017;Qian et al, 2018Qian et al, , 2020. Recently, it has been confirmed that TOR signalling functions in controlling appressorium formation in M. oryzae.…”
mentioning
confidence: 99%
“…The empty green fluorescent protein (GFP) construct was obtained in our previous work (Qian et al, 2020). The MoSLP1 DNA fragment fused with the S tag was inserted into the pXY203 construct (MoSLP1-S) containing the hygromycin resistance, and the MoERV29 DNA fragment fused with GFP (MoERV29-GFP) was inserted into the pYF11 construct containing the bleomycin (R25001; Thermo Fisher Scientific, Waltham, MA, USA) resistance gene.…”
Section: In Vivo Co-immunoprecipitation Assaymentioning
confidence: 99%
“…For complementation, the fragment containing the entire MoERV29 gene coding region and its native promoter New Phytologist (2022) 233: 1289-1302 www.newphytologist.com Ó 2021 The Authors New Phytologist Ó 2021 New Phytologist Foundation region was amplified using PCR with primers (Table S1) before insertion into pYF11 and introduced into the mutant strain. Other gene deletion mutants and corresponding complemented strains were obtained using the same strategy (Qian et al, 2020).…”
Section: Moerv29 Gene Deletion and Complementationmentioning
confidence: 99%